Awareness toward breast cancer and practice of breast self-examination among Iraqi female students at faculty of basic education - Nahed Ahmed Hassan (Wolters Kluwer Medknow Publications, 2023)
The most prevalent cancer and the one with the highest fatality rate is breast cancer, accounting for 27% of all malignancies in women and ranking one among all cancers in women. It appears that breast cancer affects both developed and developing nations. Hence, raising public awareness of breast malignancy prevention strategies is crucial in lowering the morbidity and mortality associated with the disease. The awareness and practices of female undergraduate students at Tikrit University regarding breast self-examination (BSE) were evaluated in this study. This cross-sectional investigation was performed on 420 Iraqi undergraduate scholars at the Faculty of Basic Education, University of Tikrit. The students were polled online using a self-administrated Google Forms that was disseminated through social media. Microsoft Office Excel and SPSS version 22 were used to analyze the data that had been gathered. The majority of responders (70.2%) claimed to be knowledgeable about breast cancer. Out of the participants, around 31.8% expressed the belief that a positive family history, followed by obesity 18.9% was responsible for its occurrence. BSE as a technique to find breast cancer early was only known by 33.2% of individuals who were aware of breast cancer. The significant relationships between BSE practice and breast cancer were demonstrated (P = 0.01). Timely identification and treatment of breast cancer potentially lead to improved outcomes and complete recovery when individuals promptly report signs and symptoms. By promoting awareness of breast cancer and conducting BSE, it is possible to minimize the financial burden of the treatment plan and mitigate the impact of synonyms.